Ruins of identity : - Hudson, Mark J. (University of Hawai'i Press, 1999)
In its examination of the process of ethnogenesis - the formation of ethnic groups - in the Japanese islands, this book offers an approach to ethnicity that differs fundamentally from that found in most Japanese scholarship and popular discourse. Following an extensive discussion of previous theories on the formation of Japanese language, race and culture and the nationalistic ideologies that have affected research in these topics, the author presents a model of a core Japanese population based on the dual origin hypothesis favoured by physical anthropologists. According to this model, the Jomon population, which was present in Japan by a least the end of the Pleistocene, was followed by agriculturalists from the Korean peninsula during the Yayoi period (c.400 BC-300 AD). The author analyzes further evidence of migrations and agricultural colonization in a summary of cranial, dental and genetic studies and in an examination of the linguistic and archaeological records.